Sudden losses and sudden gains during a DBT-PTSD treatment for posttraumatic stress disorder following childhood sexual abuse - Krüger, Antje; Bohus, Martin (European journal of psychotraumatology, 2014)
Background: Exposure-based treatment approaches are first-line interventions for patients suffering from posttraumatic stress disorder (PTSD). However, the dissemination of exposure-based treatments for PTSD is challenging, as a large proportion of clinicians report being concerned about symptoms worsening as a result of this type of intervention and are therefore reluctant to offer it to patients with PTSD. However, there is only little empirical evidence to date on the pattern of symptom worsening during exposure-based treatment for PTSD. Objective: The goal of the present study was to explore the frequency of sudden losses and sudden gains in the course of an exposure-based treatment programme for female patients suffering from PTSD related to childhood sexual abuse who also show severe comorbidity. In addition, the relationship between sudden changes and treatment outcome was examined. Methods: Female participants (N=74) were randomised to either a 12-week residential DBT-PTSD programme or a treatment-as-usual wait list. The pattern of symptom change was assessed via weekly assessments using the Posttraumatic Diagnostic Scale (PDS). Sudden changes were computed as suggested by the literature on sudden gains. Results: During treatment, only one participant (3%) experienced a sudden loss, whereas 25% of participants experienced sudden gains. In the waiting condition, 8% of the participants experienced sudden losses and 5% experienced sudden gains during the same time period. No symptom worsening was observed in response to exposure sessions. However, sudden gains occurred during exposure and non-exposure treatment weeks. Patients with sudden gains showed better treatment outcome in the post-treatment and follow-up assessments. Conclusions: Exposure-based treatment did not lead to PTSD symptom worsening in the study sample. Results show that sudden gains occur frequently during PTSD treatment and have a prognostic value for treatment outcome.